Understanding information systems in organizations: from Anthony’s framework to the organizational mind - Carvalho, João Álvaro (2006)
Recent developments in information technology and in information systems led to a change in the discourse about information systems in organizations: with increasing frequency, knowledge is referred to as the object that is manipulated by information systems or as the result of using them. Sometimes this change brings up some inconsistency to explanations of information systems use. This inconsistency can be viewed as a symptom of a paradigm crisis that demands a new form of viewing the information systems’ phenomena. Adding a cognitive dimension to a systemic view of organizations contributes to avoiding the inconsistency and constitutes an insight to the use of information systems in organizations. The organizational mind conceptual framework explores concepts and conceptual schemas borrowed from human cognitive studies and neurosciences and opens new perspectives for looking to information systems and information technology in organizations and in society.